Analysis of MikroTik Firewall Effectiveness in Mitigating DDoS Attacks using the Network Development Life Cycle (NDLC) Approach - M. Irsyadul 'ibad; Wildan Mahmud; Galuh Wilujeng (SISTEMASI, 2026)
This study is motivated by the increasing network security threats accompanying the growth of digital-based services in government institutions. One of the most common threats is the Distributed Denial of Service (DDoS) attack, which can cause network performance degradation and service disruption. This research aims to analyze the effectiveness of implementing a MikroTik firewall in mitigating DDoS attacks on the network of the Diskominfo Kota Kediri using the Network Development Life Cycle (NDLC) method. The research stages consisted of analysis, design, simulation, implementation, monitoring, and management. The testing process was conducted by simulating SYN Flood attacks using the Hping3 application. The evaluated parameters included throughput, delay, packet loss, and CPU utilization on the router. The experimental results showed that under DDoS attack conditions without firewall protection, throughput increased to approximately 40 Mbps, delay reached 5–15 ms, packet loss ranged from approximately 20–30%, and CPU utilization increased to 99–100%. After the firewall was implemented, network performance improved significantly, with throughput decreasing to approximately 2 Mbps, delay stabilizing below 1 ms, packet loss reduced to 0%, and CPU utilization decreasing to approximately 3%. These findings indicate that the MikroTik firewall is effective in filtering abnormal traffic and reducing system load, thereby improving network stability and maintaining service quality based on Quality of Service (QoS) parameters.